Experimental study on plate shear connector for composite construction - Chin, Chee-kiong; Ueda, Tamon; Pichai Nimityongskul; Sritawat Kitipornchai; The Royal Thai Government (Bangkok : Asian Institute of Technology, 1988)
The capacity and failure mode of plate shaped shear connector with various height and thickness, and mounted on various thickness of bed plate are studied here by u sing the direct pull- out test (see Fig.5 ) and a formula for the calculation of this capacity is proposed in the present thesis . The outcome is compared with the direct push- out test outcome as found by Slutter & Driscoll [ 3 ) and Kiyomiya & Yokota [4) . How the various sizes, shapes and arrangement of s h ear connectors may affect the joint behavior of the composite lapped splice is also presented here from two composite lapped splice beam tests in this study (see Fig.7 ) and some test results from Virach [10) . Some direct pull- out tests with the confinement of stirrups or deformed bars piercing through the shear connector (see Fig.6) are also conducted to clarify their improvement in mechanical behavior of shear connector.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Plates (Engineering); Composite construction